The Onomastic Data of the Fourteenth-Century Poll Tax Returns: A Case for Further Dialectological Study of Late Medieval English - Parkin, D. Harry (Studia Anglica Posnaniensia, 2015)
An important source of localisable Middle English dialectological data has recently become widely accessible, thanks to the published transcription of the 1377, 1379 and 1381 poll tax re-turns by Carolyn C. Fenwick (1998, 2001, 2005). As the only collection of onomastic data from the late fourteenth century with national coverage, the name forms in the records can be analysed to further our understanding of Middle English dialect distribution and change. As with many historical records, the poll tax returns are not without damage and so do not cover the country in its entirety, but provided their investigation is carried out with suitable methodological caution, they are of considerable dialectological value. Using the poll tax data, the distributions of two dialect features particular to the West Midlands (specifically rounding of /a/ to /o/ before nasals and /u/ in unstressed positions) are presented and compared with the patterns given for the same features in Kristensson’s (1987) dialect survey of data from 1290-1350. By identifying apparent discrepancies in dialect distribution from these datasets, which represent periods of no more than 100 years apart, it seems that the spread of certain Middle English dialect features may have changed considerably over a short space of time. Other possible reasons for these distribution differences are also suggested, highlighting the difficulties in comparing dialect data from differ-ent sets of records. Through this paper a case for further dialectological study, using the poll tax returns, is made, to add to the literature on Middle English dialect distribution and to improve our knowledge of ME dialect phonologies at the end of the fourteenth century.